Parenting Patterns with Receptive Language Development in Autist Spectrume Disorder (ASD) Children - Lince Amelia; Pira Ayunita; Jaka Pradika; Almumtahanah Almumtahanah; Dinarwulan Puspita; Indah Dwi Rahayu; Ditha Astuti Purnamawati (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Autism Spectrum Disorder (ASD) is a form of growth and development disorder that causes brain function not to work normally, affecting growth and development, communication skills, language development, and interaction skills. Parenting styles related to the development of receptive language in children with ASD are important considering that the mother is the closest caregiver to the child. This study aims to determine the relationship between parenting style and receptive language development in children with ASD at the Special Needs Children's Installation at the Sungai Bangkong Hospital, Pontianak. This type of research uses a correlational description with a cross-sectional approach. A sample of 48 people at the Installation for Children with Special Needs at the Sungai Bangkong Hospital, Pontianak. Most of the authoritarian parenting styles for normal receptive language development are 16,7%, while parenting styles with abnormal receptive language development are 83,3%. There is a relationship between parenting style and receptive language development in ASD children with a p-value = 0,001 <0,05. There is a relationship between parenting style and receptive language development in ASD children in the Special Needs Children's Installation at the Sungai Bangkong Hospital, Pontianak.